Managing Urban Drainage Systems with Digital Twins: Global Insights and Applications in Vietnam - Mai, Vu; Ngo, Van Yen; Pham, Quang Thanh (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study explores the transformative role of digital twin (DT) technologies in enhancing urban drainage system (UDS) management, with a dual focus on global applications and the evolving Vietnamese context. Drawing on six international case studies—Barcelona, Graz, Houston, Odense, Xi’an, and Austin—the research synthesizes best practices in real-time monitoring, predictive analytics, and integrated infrastructure management. These benchmarks are then used to evaluate five Vietnamese cities—Hanoi, Da Nang, Hue, Son La, and Cao Bang—representing a cross-section of urban scales, geographic diversity, and digital maturity. Through a mixed-methods approach combining literature review, maturity modeling, and qualitative benchmarking, the study identifies current capabilities, challenges, and opportunities for each locality. Findings highlight the varied levels of digital readiness and underscore the need for tailored strategies addressing infrastructure gaps, data integration, and human resource capacity. The study concludes with city-specific recommendations and a proposed roadmap for advancing DT-enabled UDS management in Vietnam. These insights offer implications for public policy, smart city development, environmental resilience, and educational innovation in the context of rapid urbanization and climate change adaptation.